Legal Consequences of Malpractice in the Medical World for Medical Personnel - Wardhana, Encek Muhammad Rizky Kusuma; Sulistyo, Al Qodar Purwo (Postgraduate Program in Law, Universitas Pattimura, 2025)
Introduction: This study examines the legal impact of medical accidents and malpractice on medical personnel. Through normative legal research on laws and regulations, court decisions, and related literature, this study shows that medical personnel can face various legal consequences, including civil, criminal, and administrative liability. In addition, this incident also has an impact on the reputation of the medical profession and causes fear in health workers in carrying out their duties.Purposes of the Research: This study analyzes two main issues: the legal impact on the license of medical personnel who are found guilty of malpractice, and legal protection for medical personnel in malpractice cases. In addition, they may also face civil and criminal lawsuits.Methods of the Research: Through normative legal research on laws and regulations, court decisions, and related literature, this study shows that medical personnel can face various legal consequences, including civil, criminal, and administrative liability. In addition, This study examines the legal impact of medical accidents and malpractice on medical personnel. Through normative legal research on laws and regulations, court decisions, and related literature, this study shows that medical personnel can face various legal consequences, including civil, criminal, and administrative liability.Results Main Findings of the Research: Education that focuses on improving legal and public health literacy is an urgent solution to reduce the number of inaccurate lawsuits and strengthen the relationship of mutual trust between the community and medical personnel.